The essence Phonology in Linguistic Studies - Nurul Aprilla; Tasya Nadira; Aqila Az Zahra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is basically a system of sound symbols that humans use to communicate , so the aim of teaching Indonesian is to help people better express their thoughts and feelings using good and correct language so that they can communicate well and correctly . This research is one of many theoretical studies of language , one of which is phonology . The researchers used qualitatively literature review method by collect literature , journals , articles , etc. Phonology is a subdiscipline of linguistics that investigate the sounds of language and the processes of their formation and transformation . The study of phonology includes the study of the sounds of language as a whole and their functions . “The science of phonology ” and “ the science of sound ” actually come from the Greek words “ phone ,” meaning “ sound ,” and “ logos ,” meaning “ science .” General phonology studies language sounds and phonemes . Phonology specifically studies only the sounds in one language . Phonological awareness is very important in language learning to improve reading ability . Language abilities is often associated with speaking abilities or speaking skills . The view of the